Screening of Post-Traumatic Stress Disorder among Adolescent Victims of The Garut Flash Flood in 2016 - Asy Syafa Mahfuzhah; Efri Widianti; Etika Emaliyawati (NurseLine Journal, 2021)
The flash flood that occurred in the Garut Regency three years ago brought about devastating effects, one of which was the psychological impact in adolescents, namely PTSD. This study aims at detecting the presence of PTSD in adolescent victims of the flash flood that occurred in Garut, Indonesia three years ago. PTSD screening was conducted using the PTSD Checklist (PCL) questionnaire for 102 teenagers of the State Junior High-School (SMPN) 3 Tarogong Kidul who were victims of the flood and selected using a purposive sampling technique. This study used a quantitative descriptive method with cross-sectional approach. The results showed that three years after the Garut flash flood, a total of 80% of adolescent victims did not experience PTSD and 20 (20%) of the adolescents were identified having PTSD. The highest arising symptom responses were re-experiencing (90%) and hyperarousal (80%), which involve feeling intruded by memories of disasters and increased alertness. It is expected that nurses and experts can perform early and continuous screening for PTSD following a traumatic event, both in adolescents and other age groups to prevent another more severe impact.